Oksidasi Larutan Kalium Thiosulfat dalam Ekstrak Abu Tandan Sawit dengan Udara - Gogot Haryono (Eksergi, 2008)
Potossium sulphate is a kínd offertilizer whích nowadrys is still imported. The efortþr producing itfromdiferentfeedstockwås irwestigatedby many researchers. ThÍs researchwas an ahernativeway toproducepotassium sulphatefrom ash of empty palm-bunch. This objective ofthis researchwas particularly to studythe kinetic ofoxidationreaction ofpotassium sulphate productionfrom actract of ash ofempty palm-bunch,The æperíment was conducted by/ìlling the reactor with a potassium thiosulphate solution and thereþrebubbling air from bottom of the reactor with specitìed flow røe until steady condition was attained Theproductwas ønd analyzed at several certain time intervals. Iodometric methodwas appliedþr thiosulplwteanalysis and grartimetric method for sulphate analysis The øcperimental results showed that oxidationreaction rate of thiosulphate to sulphate was controlled by the reaction step, Temperature dependence ofthe rate constant consìdered by Arrhenius'